Delayed endovascular surgery in patients with acute ST-segment elevation myocardial infarction due to massive culprit arterial thrombosis in the prevention of slow/no-reflow phenomenon - A. V. Azarov; S. P. Semitko; A. S. Zhuravlev; D. G. Ioseliani; I. Kh. Kamolov; I. S. Melnichenko; O. V. Zakharova; S. N. Puzin; I. A. Kovalchuk (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To assess whether delayed coronary artery stenting (CAS) can reduce the slow/no-reflow incidence in patients with ST-segment elevation myocardial infarction (STEMI) and massive thrombosis (TTG ≥3) of the infarct-related coronary artery (IRCA) compared with immediate CAS within primary PCI.Material and methods. Out of 3651 primary PCIs performed for acute STEMI in the period from January 2016 to May 2020 at the Mytishchi City Clinical Hospital, the retrospective analysis included 105 patients with massive IRCA thrombosis (TTG ≥3). The patients were divided into two groups: first group (n=55) — delayed CAS, second group (n=50) — immediate CAS. In the immediate CAS group, the PCI procedure ended with routine stent implantation, and in the delayed CAS group, stent implantation was delayed for at least 5 days.Results. In the delayed CAS group in comparison with immediate one, the slow/no-reflow phenomenon developed much less frequently in the form of a significant increase in the prevalence of TIMI 3 flow, better myocardial perfusion of myocardial blush grade (MBG) 2-3 (81,8 vs 64%; odds ratio (OR) 2,53; p=0,039) and ST segment resolution ≥70% (87,3% vs 58%; OR 4,97; p=0,001).Conclusion. Delayed CAS in patients with STEMI with massive thrombosis (TTG ≥3) of IRCA reduces the risk of slow/no-reflow phenomenon and can be considered as a possible alternative treatment vs immediate CAS, provided that stable coronary flow is restored before TIMI 3.